CONFLICT BETWEEN TRADITION AND RELIGION: A SOCIOLOGICAL REPRESENTATION OF HASNAN SINGODIMAYAN'S NOVELS - Heru S.P. Saputra; Sunarti Mustamar; Abu Bakar R.M.; Zahratul Umniyyah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Hasnan Singodimayan's novels express many sociological reflections on the condition of the Using community, Banyuwangi, especially regarding the conflict between tradition and religion. This study aims to examine Hasnan Singodimayan's novels to understand the ideology contained in these works. The research uses qualitative methods with a sociological approach to literature. The results showed that the author's background in the novel Kerudung Santet Gandrung sided with the traditional arts and